2018
DOI: 10.1002/anie.201811675
|View full text |Cite
|
Sign up to set email alerts
|

Reduction vs. Addition: The Reaction of an Aluminyl Anion with 1,3,5,7‐Cyclooctatetraene

Abstract: The potassium aluminyl complex K[Al(NON Ar )] (NON = NON Ar = [O(SiMe 2 NAr) 2 ] 2À ,A r = 2,6-iPr 2 C 6 H 3 ) reacts with 1,3,5,7-cyclooctatetraene (COT) to give K[Al-(NON Ar )(COT)].The COT-ligand is present in the asymmetric unit as ap lanar m 2 -h 2 :h 8 -bridge between Al and K, with additional K···p-aryl interactions to neighboring molecules that generate ah elical chain. DFT calculations indicate significant aromatic character,c onsistent with reduction to [COT] 2À . Addition of 18-crown-6c auses ar ear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
183
1
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 188 publications
(194 citation statements)
references
References 69 publications
6
183
1
4
Order By: Relevance
“…Compounds 2 and 3 are the first examples of anionic aluminanorbornadiene derivatives. Two newly formed Al−C(bridgehead) bonds of 2 and 3 [ 2 : 2.1118(15), 2.1087(15) Å; 3 : 2.1125(12), 2.1154(15) Å] are longer than those of the previously reported Al‐incorporated bicyclic compounds ( L , J , K ), reflecting the steric repulsion between four trimethylsilyl substituents and benzoannulated moiety in 2 and 3 . As a result, the C‐Al‐C angles in 2 and 3 [ 2 : 75.10(6)°; 3 : 75.21(6)°] are slightly smaller than those of reference compounds.…”
Section: Figurementioning
confidence: 83%
See 2 more Smart Citations
“…Compounds 2 and 3 are the first examples of anionic aluminanorbornadiene derivatives. Two newly formed Al−C(bridgehead) bonds of 2 and 3 [ 2 : 2.1118(15), 2.1087(15) Å; 3 : 2.1125(12), 2.1154(15) Å] are longer than those of the previously reported Al‐incorporated bicyclic compounds ( L , J , K ), reflecting the steric repulsion between four trimethylsilyl substituents and benzoannulated moiety in 2 and 3 . As a result, the C‐Al‐C angles in 2 and 3 [ 2 : 75.10(6)°; 3 : 75.21(6)°] are slightly smaller than those of reference compounds.…”
Section: Figurementioning
confidence: 83%
“…The NacNac‐stabilized Al I species B underwent (1+2) cycloaddition with alkynes and alkenes to form Al‐containing three‐membered ring species G . The diamino–Al anion D cyclized with cyclooctatetraene to give H via (1+2) cycloaddition . Similarly, the monomeric form of oxygen‐stabilized Al anion F reacted with ethylene to form (1+2) cycloadduct I .…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, three types of anionic and nucleophilic aluminum species have been reported recently and used as an Al I species in a low oxidation state . It should be noted here that the base‐stabilized aluminum anion was used for the synthesis of a base‐stabilized alumanylgold complex (see class‐(iii) complexes above) through a nucleophilic substitution at the gold center .…”
Section: Methodsmentioning
confidence: 99%
“…Notwithstanding this limitation, pioneering work has shown that aneutral dialumene activates CO 2 to give the aluminumcarbonate (VI)a nd -carbonyl (VII)c omplexes. Recent advances in group 13 chemistry have led to the development of new nucleophilic sources of aluminum [17] and indium. [16] Theu tilization of aluminum in this area is particularly attractive due to its low cost and high terrestrial abundance.…”
mentioning
confidence: 99%